Programming Models for Reconfigurable Application Accelerators - MANZKE, MICHAEL; BRENNAN, ROSS; WOULFE, MUIRIS; CREEDON, EOIN TIMOTHY (Barcelona Supercomputing Center, 2009)
Algorithms can be accelerated by offloading computeintensive operations to application accelerators comprising reconfigurable hardware devices known as Field Programmable Gate Arrays (FPGAs). We examine three types of accelerator programming model ? master-worker, message passing and shared memory ? and a typical FPGA system configuration that utilises each model. We assess their impact on the partitioning of any given algorithm between the CPU and the accelerators. The ray tracing algorithm is subsequently used to review the advantages and disadvantages of each programming model. We conclude by comparing their attributes and outlining a set of recommendations for determining the most appropriate model for different algorithm types.
1st Workshop on Programming Models for Emerging Architectures (PMEA 2009)
PUBLISHED
Raleigh, North Carolina, USA
Keywords: Computer Science